2010
DOI: 10.1113/expphysiol.2009.050245
|View full text |Cite
|
Sign up to set email alerts
|

Is oxidative stress a cause or consequence of disuse muscle atrophy in mice? A proteomic approach in hindlimb‐unloaded mice

Abstract: Two-dimensional proteomic maps of soleus (Sol), a slow oxidative muscle, and gastrocnemius (Gas), a fast glycolytic muscle of control mice (CTRL), of mice hindlimb unloaded for 14 days (HU mice) and of HU mice treated with trolox (HU-TRO), a selective and potent antioxidant, were compared. The proteomic analysis identified a large number of differentially expressed proteins in a pool of ∼800 proteins in both muscles. The protein pattern of Sol and Gas adapted very differently to hindlimb unloading. The most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
135
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(147 citation statements)
references
References 75 publications
11
135
0
1
Order By: Relevance
“…We further postulated that attenuation of oxidative stress would mitigate translocation of nNOS from the sarcolemmal region and significantly ameliorate two predominant phenotypic changes that begin early in mechanical unloading: 1) muscle fiber atrophy and 2) fibertype shift from slow to fast. Previous antioxidant supplementation studies using nonspecific scavengers have yielded inconsistent findings in reducing morphological responses to unloading (3,6,20). In contrast, transfection of the antioxidant enzyme catalase yielded significant protection against atrophy (9).…”
mentioning
confidence: 90%
“…We further postulated that attenuation of oxidative stress would mitigate translocation of nNOS from the sarcolemmal region and significantly ameliorate two predominant phenotypic changes that begin early in mechanical unloading: 1) muscle fiber atrophy and 2) fibertype shift from slow to fast. Previous antioxidant supplementation studies using nonspecific scavengers have yielded inconsistent findings in reducing morphological responses to unloading (3,6,20). In contrast, transfection of the antioxidant enzyme catalase yielded significant protection against atrophy (9).…”
mentioning
confidence: 90%
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 However, this approach has been demonstrated widely useful in a number of recent works [27][28][29][30].…”
Section: Page 5 Of 47mentioning
confidence: 99%
“…The downregulation of glycolytic enzymes is a symptom of energy production failure, and can contribute to muscle damage. Interestingly a general impairment of energy metabolism have been observed in conditions of muscle atrophy [29], which may develop also during statin myopathy [50]. Moreover, it has been shown that hereditary muscle glycogenoses in humans are characterized by defective glycolytic enzymes, including beta enolase, and leads to different degree of myopathy, ranging from cramps to myoglobinuria [51][52].…”
Section: Glycolytic Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other studies reporting that administration of vitamin E (a small molecule antioxidant) results in decreased lipid peroxidation in skeletal muscle (Kondo et al, 1991;Servais et al, 2007). The reduced iliofibularis lipid peroxidation in aestivation when TAC is also reduced, and no reduction of gastrocnemius lipid peroxidation in aestivation when TAC is reduced at 24°C or increased at 30°C, suggests a different suite of in vivo conditions between the two muscles, such as muscle-specific regulation of other antioxidants, mitochondrial properties, degree of coupling of ROS formation to oxygen consumption and differences in the signalling requirements and metabolic program changes of the muscles (Anderson and Neufer, 2006;Brocca et al, 2010).…”
Section: Oxidative Damage Lipid Peroxidationmentioning
confidence: 99%